The influence of obesity on survival in early, high-risk breast cancer: results from the randomized SUCCESS A trial. Issue 1 (December 2015) - Widschwendter, Peter; Friedl, Thomas; Schwentner, Lukas; DeGregorio, Nikolaus; Jaeger, Bernadette; Schramm, Amelie; Bekes, Inga; Deniz, Miriam; Lato, Krisztian; Weissenbacher, Tobias; Kost, Bernd; Andergassen, Ulrich; et al.
Abstract Introduction Obese breast cancer patients have worse prognosis than normal weight patients, but the level at which obesity is prognostically unfavorable is unclear. Methods This retrospective analysis was performed using data from the SUCCESS A trial, in which 3754 patients with high-risk early breast cancer were randomized to anthracycline- and taxane-based chemotherapy with or without gemcitabine. Patients were classified as underweight/normal weight (body mass index (BMI) < 25.0), overweight (BMI 25.0–29.9), slightly obese (BMI 30.0–34.9), moderately obese (BMI 35.0–39.9) and severely obese (BMI ≥ 40.0), and the effect of BMI on disease-free survival (DFS) and overall survival (OS) was evaluated (median follow-up 65 months). In addition, subgroup analyses were conducted to assess the effect of BMI in luminal A-like, luminal B-like, HER2 (human epidermal growth factor 2)-positive and triple-negative tumors. Results Multivariate analyses revealed an independent prognostic effect of BMI on DFS (p  = 0.001) and OS (p  = 0.005). Compared with underweight/normal weight patients, severely obese patients had worse DFS (hazard ratio (HR) 2.70, 95 % confidence interval (CI) 1.71–4.28, p  < 0.001) and OS (HR 2.79, 95 % CI 1.63–4.77, p  < 0.001), while moderately obese, slightly obese and overweight patients did not differ from underweight/normal weight patients with regard to DFS or OS. Subgroup analyses showed a similar significant effect of BMI on DFS and OS in patients with triple-negative breast cancer (TNBC), but not in patients with other tumor subtypes. Conclusions Severe obesity (BMI ≥ 40) significantly worsens prognosis in early breast cancer patients, particularly for triple-negative tumors. Trial registration Clinicaltrials.govNCT02181101 . Registered September 2005.